Korelasi antara perhatian orang tua dan disiplin belajar terhadap motivasi belajar matematika mahasiswa - Fitriani, Fitriani; Elisa, Elisa; Rossiah, Rossiah; Lubis, Rahmat Sholih (Mahesa Research Center, 2024)
This study investigates the correlation between parental attention and study discipline with students' motivation to learn mathematics. The research employs a descriptive quantitative approach, utilizing path analysis, which includes correlation analysis followed by regression analysis. The results reveal a correlation coefficient of 0.844 between parental attention, study discipline, and student's motivation to learn mathematics, categorizing it as